Arteriovenous Fistula: An Unusual Complication of Orthognathic Surgery—Case Report and a Brief Review - Josue Gallardo-Caudillo; Freddy Andrés Vivero-Alcivar; Cinthya María Quisiguiña-Salem; Sergio Esquivel-Martin (Case Reports in Dentistry)
Arteriovenous fistulas rarely occur in the head and neck region. They typically arise from blunt or penetrating trauma but can develop as an uncommon complication following bimaxillary orthognathic surgery, a procedure to correct jaw deformities. This report describes a male patient who experienced an arteriovenous fistula after orthognathic surgery. We detail the diagnosis through patient symptoms and imaging, along with successful treatment via endovascular embolization. We also follow the patient for 1 year. This case highlights the importance of recognizing this rare complication to ensure prompt diagnosis and intervention. We discuss key points for preventing, diagnosing, and effectively treating arteriovenous fistulas after orthognathic surgery.